The Subjective Evaluation of Health Status of Multimorbid Patients in Primary Health Care - Steponkutė, Justina; Mažionienė, Asta (Slauga. Mokslas ir praktika, 2023)
Abstract. Society who is getting older and the increase of multimorbidity spread amongst it shows that the number of patients who suffer from more than two chronic diseases will increase. Multimorbidity makes life difficult for patients because their possibilities of functioning decreases and this also determines their inferior evaluation of health status. For the self – assessment of health status of multimorbid patients in primary health care context their own perception, personal qualities and factors which not belonging from patients, such as age or gender, have huge influence. The aim of the study – to evaluate health status of multimorbid patients in primary health care by subjective attitude of patients.Research methods. A written survey was conducted for quantitative research. Research participants were the persons (n = 371) diagnosed with two or more chronic diseases.Results. According to the research data, in most cases multimorbid patients in primary health care, by their subjective evaluation, did not have problems with mobility, self – care and doing usual activities, but they felt slight pain or discomfort and slight anxiety or depression. Women, older patients, patients with lower education, patients who live alone and also patients who stated being diagnosed with more chronic diseases, self – assessed their health status significantly worse.
Keywords: primary health care; multimorbidity; health status